ANALISIS PERSEPSI MASYARAKAT TENTANG PELAYANAN BUS TRANSKOETARADJA DAN LABI-LABI DI KOTA BANDA ACEH (STUDI KASUS : KORIDOR I PUSAT KOTA – DARUSSALAM) - Hanyta Khairunnisa; Renni Anggraini; Muhammad Isya (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
Transportation services in the city of Banda Aceh are currently supported by a public transport system, one of which is Transkoetaradja bus and labi-labi. At the beginning of its service, Transketaradja bus public transportation received a fairly good response from the community. To find out how Transkoetaradja buses can improve their service capabilities, then a study is needed that can convey information. The purpose of this study was to analyze the level of Transkoetaradja bus and labi-labi service. The method used is a quadrant analysis method by distributing questionnaires to 381 Transkoetaradja bus and labi-labi passengers. Based on the conclusions obtained, the performance of public transport in the city of Banda Aceh is currently in the medium category, because in some assessment parameters there are those that need to be improved again, and if seen from the quality of each parameter being examined, Transkoetaradja buses are better than labi-labi. The results show that not all factors are in quadrant A, which states that not all attributes are factors that influence the performance of Transkoetaradja buses and labi-labi. Of the 10 factors, only 6 factors are found in quadrants A and B for Transkoetaradja buses while the turtles have 7 factors. These factors include: rush hour, outside rush hour, travel speed, headway, travel time, service time, frequency, number of vehicles, waiting time and the start and end of the trip.